Combination of Alprazolam and Bailemian Capsule Improves the Sleep Quality in Patients With Post-Stroke Insomnia: A Retrospective Study - Wang, Jian; Wang, Zhiqiang; Wang, Xiaoyan; Du, Guo; Zheng, Bo; Li, Yuxia; Wang, Qingsong (Frontiers in Psychiatry, 2019)
Insomnia is often ignored in the diagnosis and treatment of patients after stroke. The present study aimed to evaluate the efficacy of alprazolam (ALP) combined with Bailemian capsule (BC, a traditional Chinese patent medicine) in the treatment of post-stroke insomnia (PSI). A total of 231 stroke patients involved in this retrospective study were treated by ALP, BC, or ALP + BC for 3 weeks. The quality of sleep was evaluated by the Pittsburgh sleep quality index (PSQI) and polysomnography (PSG), while self-care ability was monitored by the modified Rankin Scale (mRS) before and after treatment. Compared to the baseline, the self-care ability of patients in each group was significantly improved after treatment (P<0.01). The PSQI data showed a significant improvement in all patients in all of the subjective PSQI items and global score (P<0.05). Notably, ALP+BC administration had a significantly greater effect on sleep latency, quality, disturbance, and efficiency, as well as daytime dysfunction and global PSQI than the use of ALP or BC alone (P<0.05). The PSG data showed that ALP significantly improved the sleep efficiency and decreased the arousal times, REM sleep and sleep latency (P<0.05), while BC significantly improved the sleep efficiency, total sleep time and the duration of N3 (P<0.05). Strikingly, ALP+BC achieved the effect of both ALP and BC (P<0.05). Importantly, the effect of the combination of ALP and BC was greater than the use of ALP or BC alone, which was consistent with the result of PSQI. In conclusion, the sleep quality and self-care ability of patients with PSI were improved by ALP and BC, thereby supporting the potential advantages of ALP combined with BC in the treatment of patients with PSI.